Frequencies of Behavioral Problems Reported by Parents and Teachers of Hearing-Impaired Children With Cochlear Implants - Boerrigter, Merle; Vermeulen, Anneke; Marres, Henri; Mylanus, Emmanuel; Langereis, Margreet (Frontiers in Psychology, 2019)
Background: Internalizing and externalizing behavioral problems were frequently reported in profoundly hearing-impaired (HI) children with hearing aids. Due to the positive effect of cochlear implants (CIs) on hearing and language development, a positive effect on behavioral problems was expected. However, there is no consensus about the frequency of behavioral problems in CI children, and studies are often based on one informant with the risk of missing behavioral problems in other contexts. Aims: The first aim of this study was to investigate the frequency of behavioral problems in children with CIs as compared to a hearing normative sample. The second aim was to measure the agreement between the parents’ and teachers’ rates on the behavioral problem scales. And the third aim was to investigate the relation between speech perception, language skills and the frequencies of reported behavioral problems. Methods: Of 71 CI children, 51% were girls and 49% were boys, and the mean age was 8.6 (SD = 3.3). Behavior was reported by parents using the Child Behavior Checklist (CBCL) and by teachers using the Teacher Report Form (TRF). Frequencies of behavioral problems of CI children (6–16 years) were compared to a normative sample with the chi square test. Parent-teacher agreement was measured with the intraclass correlation coefficient (ICC 2,1). Next CI children were divided into four ability level categories regarding speech perception and language skills. Frequencies of behavioral problems were compared between the categories with the chi square test. Results: Parents and teachers of CI children reported similar frequencies of behavioral problems to the normative sample. Fair to low parent-teacher agreements were found on the behavioral problem scales. A significantly higher frequency of behavioral problems was reported in children with low speech perception and receptive vocabulary at school. Conclusion: Parents and teachers report similar frequencies of behavioral problems children with CIs compared to a hearing normative sample. Children with lower speech perception and language levels are more at risk of developing behavioral problems at school. Adequate speech perception and language levels are found to be protective factors for the development of behavior.